2015
DOI: 10.1007/s00268-015-3075-8
|View full text |Cite
|
Sign up to set email alerts
|

The Tight Adaptation at Pancreatic Anastomosis Without Parenchymal Laceration: An Institutional Experience in Introducing and Modifying the New Procedure

Abstract: A unique concept of Blumgart pancreatic anastomosis, i.e., utilizing the jejunum as an interstitial cushion to prevent pancreatic laceration at the knot site, has become realistic through a simple "one step" modification. This technique, also providing flexible handling space at main pancreatic duct anastomosis, should contribute to the improved PF prevention and shortening the POHS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 38 publications
0
38
1
1
Order By: Relevance
“…As shown in previous reports, male sex and a BMI of > 22 kg/m 2 were risk factors for CR-PF [ 17 ] in our study. Unlike in previous reports [ 7 , 8 , 18 ], there was no significant difference in the incidence of CR-PF between the Kakita and Blumgart anastomosis groups. Our hypothesis that Blumgart anastomosis is associated with a lower incidence of whole PF and higher incidence of latent PF was denied in this study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…As shown in previous reports, male sex and a BMI of > 22 kg/m 2 were risk factors for CR-PF [ 17 ] in our study. Unlike in previous reports [ 7 , 8 , 18 ], there was no significant difference in the incidence of CR-PF between the Kakita and Blumgart anastomosis groups. Our hypothesis that Blumgart anastomosis is associated with a lower incidence of whole PF and higher incidence of latent PF was denied in this study.…”
Section: Discussioncontrasting
confidence: 99%
“…In recent decades, a new standardized U-suture technique, which was originally described by Blumgart et al [ 5 , 6 ] in 2000, has been improved and rapidly accepted. Several studies have demonstrated the superiority of Blumgart anastomosis over Kakita anastomosis [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The early identification of patients at a high risk for clinically relevant POPF can increase the accuracy of preoperative benefit/risk assessment and the information given to patients. Furthermore, early identification should be useful for guiding technical and pharmacologic management practices, including perioperative nutritional support, imaging examinations for the early detection of abdominal abscesses, infection control, drainage tube management, and the administration of somatostatin analogs [11-13]. …”
Section: Discussionmentioning
confidence: 99%
“…Ideally, predictive factors should be determined preoperatively by objective parameters. Preoperative identification of patients at high risk of clinically relevant POPF can increase the accuracy of preoperative benefit/risk assessment and information given to patients and should enable surgeons to modify surgical procedures and perioperative management to reduce risk [11-13]. …”
Section: Introductionmentioning
confidence: 99%
“…Two major PJ reconstructions of Kakita method and Blumgart's technique have been reported [18][19][20][21]. Oda et al reported that the rate of ISGPF grade B+C PF was 29/78 (37.2%) in the Kakita group and 16/78 (20.5%) in the Blumgart group (P = 0.033) [22]. The principal technique of these two methods is a tight adaptation of pancreatic parenchyma and duodenal seromusuclaris.…”
Section: Groupmentioning
confidence: 99%